Zur Kenntnis der Ruteliden Süd-Chinas (Coleoptera: Scarabaeidae, Rutelinae). - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Actsfukiensis Machatschke, 1955 (Anomala), spec. n.fukiensis Machatschke, 1955 (Mimela), spec. n.klapperichi Machatschke, 1955 (Mimela), spec. n.kuatuna Machatschke, 1955 (Mimela), spec. n.fukiensis Machatschke, 1955 (Popillia), spec. n.